Public support for cigarette price increase in Indonesia. Issue 3 (18th December 2020) - Nurhasana, Renny; Ratih, Suci Puspita; Dartanto, Teguh; Moeis, Faizal Rahmanto; Hartono, Risky Kusuma; Satrya, Aryana; Thabrany, Hasbullah
Abstract : Background: The current tobacco control policies in Indonesia are known to be ineffective in reducing tobacco consumption. Therefore, increasing cigarette prices is one of the effective instruments that should be supported by governments and society. This study aims to assess public support for cigarette price increases as well as to generate scientific evidence for the government and policymakers. Method: This cross-sectional survey obtained data through telephone interviews with 1000 respondents aged ≥18 years old in Indonesia. The interviews started from 1 May 2018 to 31 May 2018. Result: Respondents were varied in terms of age, gender, level of education, income, occupation, area of living and smoking status. This study found that 87.9% of the respondents including 80% of smokers support cigarette price increase to prevent children from buying cigarettes. Approximately 74.0% of smokers said they would stop smoking if cigarette prices were Rp70 000 (US$5) per package. The multivariate analysis revealed that age, income, money spent on cigarettes per day and the perception of current cigarette prices are the factors influencing support for higher cigarette prices. Conclusion: The increase in cigarette prices is supported by society at large, including active smokers. The government must consistently adjust cigarette prices through an excise taxing and cigarette retail price mechanism. Governments, academicians, non-governmental organisations and tobacco control activists should generate a unified understanding that increasing cigarette prices will improve overall life quality.